The role of community benefits in community acceptance of multifunctional solar farms in the Netherlands. (November 2022) - van den Berg, Kimo; Tempels, Barbara
Abstract: While solar farm developments contribute to sustainable energy goals, they often face high levels of local opposition due to their expected negative impacts on the direct environment. Community benefits are a promising tool to reduce local opposition, as they have proven to do so in wind farm developments. By adding multiple functions to a solar farm, benefits for the local community - other than sustainable energy production - can be generated. However, also examples exist where community benefits have not managed to reduce levels of opposition. Therefore, this research aims to understand the role of community benefits in community acceptance of multifunctional solar farm developments through case studies in the Netherlands. The research consists of two phases: an exploratory phase through desk research mapping multifunctional solar farm developments in the Netherlands and an explanatory phase, analysing why community benefits are implemented and how they affect community acceptance, done through interviews. The results show that a key factor determining if community benefits contribute to community acceptance is the extent to which these benefits meet the experienced needs of a community. The degree to which solar farm developments succeed in meeting these needs depends on the motives and interest of developers to provide benefits, the history and context of the location and the level of community involvement. When the community feels like the benefits meet their needs, community acceptance is increased. However, when the compensation offered does not meet these needs, it negatively influences trust and thus leads to more resistance. Highlights: Community benefits are promising to reduce local opposition to solar farms. Multifunctional solar farms are a spatial model to provide community benefits. In community acceptance, the distribution of costs and benefits is important. Community benefits increase acceptance of solar farms if they meet the local needs.